Budget Planning and Internal Control on Local Financial Accountability: Mediating Budget Absorption - Rahmawati, Rahmawati; Ibrahim, Ibrahim; Irma, Irma; Bunyamin, Bunyamin; Dahlan, Ahmad (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study analyzes budget planning and internal control of regional financial accountability through budget absorption at the Regional Planning, Development, Research and Development Agency of South Sulawesi Province. The research design used in this study is Correlational Research and path analysis with a quantitative approach to determine the direct and indirect effects on the variables studied. The sampling of this research was conducted by purposive sampling method with a total sample of 102 employees. The results showed that budget planning, internal control, and budget absorption positively affected accountability in the Regional Planning, Development, Research and Development Agency of South Sulawesi Province. The results of this study can also be used for researchers and further researchers as well as parties who need it as a source of reference and helpful information in adding insight into issues related to budget planning, internal control, financial accountability, and budget absorption.